Synaptic changes induced by cannabinoid drugs and cannabis use disorder - Shana M. Augustin; David M. Lovinger (Neurobiology of Disease, 2022)
The legalization of cannabis in many countries, as well as the decrease in perceived risks of cannabis, have contributed to the increase in cannabis use medicinally and recreationally. Like many drugs of abuse, cannabis and cannabis-derived drugs are prone to misuse, and long-term usage can lead to drug tolerance and the development of Cannabis Use Disorder (CUD). These drugs signal through cannabinoid receptors, which are expressed in brain regions involved in the neural processing of reward, habit formation, and cognition. Despite the widespread use of cannabis and cannabinoids as therapeutic agents, little is known about the neurobiological mechanisms associated with CUD and cannabinoid drug use. In this article, we discuss the advances in research spanning animal models to humans on cannabis and synthetic cannabinoid actions on synaptic transmission, highlighting the neurobiological mechanisms following acute and chronic drug exposure. This article also highlights the need for more research elucidating the neurobiological mechanisms associated with CUD and cannabinoid drug use.